The cerebellum and its disorders - Manto, Mario; Pandolfo, Massimo (Cambridge : Cambridge University Press, 2002)
Recent years have seen major advances in the understanding of motor and non-motor operations of the cerebellum, including its role in cognition, and important discoveries in the genetics of the cerebellar ataxias. This is a comprehensive text on the cerebellum and its disorders. It ranges from embryology and basic neuroanatomy to a thorough survey of the sporadic and hereditary disorders of the cerebellum. Models of cerebellar function and clinical-pathophysiological correlations are thoroughly covered, and there is an extensive and authoritative review of recent advances in the genetics of cerebellar diseases. The chapters are written by the leading international authorities on the cerebellum, including many of those who made fundamental discoveries in the field. The first comprehensive text on the cerebellum to be published for many years, this book will be essential reading for a wide range of basic and clinical neuroscientists, neurologists and others studying or treating cerebellar disorders.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cerebellum; Cerebellum -- Diseases